Assessing the validity and reliability of the Arabic versions of Mini Asthma Quality of life questionnaire and Asthma Control Test in adult patients with asthma: A factor analysis study - Walid Al-Qerem; Anan Jarab; Abdel Qader Al Bawab; Alaa Hammad; Jonathan Ling; Fawaz Alasmari; Khaled Al Oweidat; Sarah Ibrahim (Elsevier, 2023)
Background and objective: Asthma is a common disease that has a significant influence on patients' quality of life. Although Arabic tools for assessing symptom control and quality of life in individuals with asthma are available, no sufficient studies have evaluated the validity of these tools. Therefore, the aim of the current study was to validate the Arabic version of these tools. Methods: Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were conducted on the Arabic versions of the Asthma Control Test (ACT) and Mini Asthma Quality of Life Questionnaire (Mini AQLQ). Results: A total of 314 participants (70.1 % females) were enrolled in the current study. The mean age of the participants was 51.47 (±16.37). EFA suggested a three-factor model for Mini AQLQ and a one-factor model for ACT, which was confirmed by CFA analyses. High correlations were found between spirometric values and ACT and Mini AQLQ scores, indicating good concurrent validity. The area under the curve produced by the Roc curve was 0.861 (p < 0.001), and the most suitable cut-off point was 4.741. Conclusion: All analyses conducted showed that the Arabic versions of both Mini AQLQ and ACT are reliable and valid and can be administered to adults with asthma. The application of these validated instruments will improve the management and diagnosis of asthma in Arab countries.